Flake size-dependent adsorption of graphene oxide aerogel - Soon, Poh Lee; Ali, Gomaa A. M.; Algarni, H.; K. F., Chong (Elsevier, 2019)
In this work, the flake size-dependent adsorption kinetics of graphene oxide (GO) aerogel is studied. GO in different flake sizes are produced by sonication prior to the preparation of aerogel through freeze-dry method. The structural characterizations reveal that GO aerogel with smaller flake size possesses higher surface area and higher intensity of edge-plane oxygen functionalities. These provide more adsorption sites and active sites for heavy metal ions adsorption. Adsorption study reveals the higher Fe3+ ions adsorption capacity as well as uptake rate on GO aerogel with smaller flake size. The adsorption kinetic obeys the pseudo-second-order kinetic model which indicates the chemisorption is the rate-determining step. Adsorption isotherms of GO aerogel on Fe3+ ions show highest Langmuir adsorption capacity of 133.3 mg/g and render it to be a potential material for heavy metal ions removal in wastewater treatment.